2012
DOI: 10.1111/jsr.12003
|View full text |Cite
|
Sign up to set email alerts
|

Shiftworkers report worse sleep than day workers, even in retirement

Abstract: SUMMARY The aim of this study was to explore how the level of shiftwork exposure during an individual’s working life might be related to subjectively reported sleep quality and timing during retirement. Telephone interviews regarding past employment and sleep timing and quality (among other variables) were conducted using a pseudo-random age-targeted sampling process. Subjective sleep quality was assessed using a telephone version of the Pittsburgh Sleep Quality Index. Timing of reported habitual bedtimes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 18 publications
3
46
0
2
Order By: Relevance
“…The night-shift workers in the present study reported worse sleep quality compared with non-night-shift workers, consistent with findings from a previous study 31. It is hypothesised that short sleep duration increases body weight and glucose metabolism, whereby short sleep duration is believed to increase ghrelin and decrease leptin concentration, leading to an increase in appetite and weight gain 32.…”
Section: Discussionsupporting
confidence: 91%
“…The night-shift workers in the present study reported worse sleep quality compared with non-night-shift workers, consistent with findings from a previous study 31. It is hypothesised that short sleep duration increases body weight and glucose metabolism, whereby short sleep duration is believed to increase ghrelin and decrease leptin concentration, leading to an increase in appetite and weight gain 32.…”
Section: Discussionsupporting
confidence: 91%
“…The extreme difficulty to maintain an adequate sleep-wake function while working in shifts, due to circadian misalignment, is diagnosed as SWSD (Drake et al 2004). Recent studies show that SWSD can be a chronic condition, as evidenced by measurements in retired shift workers (Rotenberg et al 2011;Monk et al 2013). The present results may be interpreted within the view that disturbed sleep is a factor in the causative pathway from shift work to deteriorating health (Puttonen et al 2010;Rajaratnam et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Our case, combined with the previous 6/12 report [6], suggests that chronic non-circadian military-shift schedules may result in circadian arrhythmia. This further highlights the potential long-term effects of extreme shiftwork on sleep [7,8]. From a clinical perspective, when sleepiness is out of proportion to other findings (i.e.…”
Section: Discussionmentioning
confidence: 99%